Malnutrition in Stroke Patients: Risk Factors, Assessment, and Management - Sabbouh, Toni; Torbey, Michel T. (Neurocritical care, 2018)
[...]the hasty identification of malnutrition using body mass index (BMI) or anthropometric measures or laboratory parameters after the acute event is fundamental to avoid poor outcomes [10, 14, 15]. In the acute stage of stroke, dysphagia occurs in 30–50% of the patients and leads to a 12-fold increase in developing aspiration pneumonia and subsequent malnutrition [16, 23, 24]. [...]the presence of cognitive impairments, visual, language, and speech deficits can hinder effective communication about food preference and satiety leading to malnutrition [14]. In the absence of infection and inflammation, serum albumin level can give a fair estimate of the nutritional status [14]. [...]CRP has been found to predict vasospasms and long-term outcome in SAH patients [33, 34]. According to several studies [11, 39, 40], being at high risk of malnutrition, as assessed by MUST, is a significant independent predictor of mortality, length of hospitalization, and hospitalization costs at 6 months post-stroke.